Subgrades Stabilization of Kuantan Clay Using Fly Ash and Bottom Ash - Achmad Fauzi, Abdul Wahab; Wan Mohd Nazmi, Wan Abdul Rahman; Usama Juniansyah, Fauzi (2010)
The main objective of this study is the utilization of fly ash and bottom ash to improve the sugbrades material in highway construction. The research conducts various contents of fly ash and bottom ash to different types of clay soils from various sites in Kuantan. The compaction tests and California Bearing Ratio (CBR) tests were applied in soil samples to estimate the optimum mixture design. The samples were set up by mixing soil samples with various content of fly ash and bottom ash at different water content in compaction test to obtain optimum dry unit weight and optimum water contents. This optimum water contents were used in CBR tests of mixtures of soil samples-fly ash/bottom ash. The accomplishment of subgrade stabilization depends on the engineering properties of soils and characteristic of fly ash and bottom ash. The performance analysis of ﬂy ash and bottom ash should be based on the laboratory tests such as engineering properties of soil, compaction and CBR tests of a speciﬁc site in Kuantan. The strength gain in stabilization mainly depends on two factors: fly ash and bottom ash content and molding water content. The variation content of fly ash and bottom ash were 4%, 8% and 12% by total weight.